SP2.2.14Evaluating the benefits of increasing exposure to the operating theatre for Foundation Year One Trainees in General Surgery. (28th October 2021) - Fardanesh, Armin; Boardman, Charlotte; Al-Whouhayb, Maitham; Mathur, Pawan; Klein, Martin
Abstract: Aims: Many foundation year one (FY1) doctors report little exposure to the operating theatre. Surgical departments welcome FY1s in theatres, but ward duties often prevent them from achieving direct exposure to operations. Following the implementation of specific days on the timetable dedicated to attending the operating theatre, this project aimed to reflect on the impact on FY1 training in General Surgery. Methods: Structured interviews were held with the 9 FY1 doctors who were 2 months into their rotation in General Surgical block. Results: All FY1s believed that assisting in operations added to their experience of the specialty. They reported increased understanding of the procedures and recovery pathways for their patients, which improved their ability to manage these patients peri-operatively. As expected, seven FY1s confirmed that they did not have the opportunity on non-allocated days to attend theatre due to "being busy on the ward" and not wanting to "give the others more work". Two FY1s who intend on pursuing a career in surgery described additional benefits including the opportunity to gain practical skills and build a surgical logbook. Conclusion: One of the main barriers for FY1s wanting to attend theatre sessions is an excessive ward workload. By allocating theatre days on the rota this challenge was overcome and the benefits of attending theatre are evident. Regular exposure to the operating theatre improves foundation training in General Surgery by increasing understanding and confidence in managing surgical patients and assisting prospective surgical applicants with early, supervised surgical skills practice.